Membrane-binding domains and cytopathogenesis of the matrix protein of vesicular stomatitis virus. - Ye, Z (1994)
The membrane-binding affinity of the matrix (M) protein of vesicular stomatitis virus (VSV) was examined by comparing the cellular distribution of wild-type (wt) virus M protein with that of temperature-sensitive (ts) and deletion mutants probed by indirect fluorescent-antibody staining and fractionation of infected or plasmid-transfected CV1 cells. The M-gene mutant tsO23 caused cytopathic rounding of cells infected at permissive temperature but not of cells at the nonpermissive temperature; wt VSV also causes rounding, which prohibits study of M protein distribution by fluorescent-antibody staining. Little or no M protein can be detected in the plasma membrane of cells infected with tsO23 at the nonpermissive temperature, whereas approximately 20% of the M protein colocalized with the membrane fraction of cells infected with tsO23 at the permissive temperature. Cells transfected with a plasmid expressing intact 229-amino-acid wt M protein (M1-229) exhibited cytopathic cell rounding and actin filament dissolution, whereas cells retained normal polygonal morphology and actin filaments when transfected with plasmids expressing M proteins truncated to the first 74 N-terminal amino acids (M1-74) or deleted of the first 50 amino acids (M51-229) or amino acids 1 to 50 and 75 to 106 (M51-74/107-229). Truncated proteins M1-74 and M51-229 were readily detectable in the plasma membrane and cytosol of transfected cells as determined by both fluorescent-antibody staining and cell fractionation, as was the plasmid-expressed intact wt M protein. However, the expressed doubly deleted protein M51-74/107-229 could not be detected in plasma membrane by fluorescent-antibody staining or by cell fractionation, suggesting the presence of two membrane-binding sites spanning the region of amino acids 1 to 50 and amino acids 75 to 106 of the VSV M protein. These in vivo data were confirmed by an in vitro binding assay in which intact M protein and its deletion mutants were reconstituted in high- or low-ionic-strength buffers with synthetic membranes in the form of sonicated unilammelar vesicles. The results of these experiments appear to confirm the presence of two membrane-binding sites on the VSV M protein, one binding peripherally by electrostatic forces at the highly charged NH2 terminus and the other stably binding membrane integration of hydrophobic amino acids and located by a hydropathy plot between amino acids 88 and 119.